156k views
1 vote
Please solve-3(×-2)=2(×-7) and write a reason for each step ​

Please solve-3(×-2)=2(×-7) and write a reason for each step ​-example-1
User Noinput
by
5.3k points

1 Answer

3 votes
-3(x - 2) = 2(x - 7) remove the parentheses
-3x + 6 = 2x - 14. Move the terms
-3x - 2x = -14 - 6. Collect like terms. Calculate.
-5x = -20. Divide both sides.
Solution: x = 4
User Ilkay
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.